THE APOLOGY STRATEGIES USED BY THE WORKERS TO THE OLD AND YOUNG BOSSES - Lili Chen; Josefa J. Mardijono (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This study is aimed to reveal the type of apology strategies used by the workers to the old and young bosses. There were five workers and two bosses, old and young bosses, taken for the subjects. Finally, the research came up with the result that the way of the workers apologizing might influenced by the age of the bosses as interlocutor which made the workers produce apology utterances in different ways of apology to the old and young bosses.